2013
DOI: 10.1038/ncomms3676
|View full text |Cite
|
Sign up to set email alerts
|

A correlated nickelate synaptic transistor

Abstract: Inspired by biological neural systems, neuromorphic devices may open up new computing paradigms to explore cognition, learning and limits of parallel computation. Here we report the demonstration of a synaptic transistor with SmNiO 3 , a correlated electron system with insulator-metal transition temperature at 130°C in bulk form. Non-volatile resistance and synaptic multilevel analogue states are demonstrated by control over composition in ionic liquid-gated devices on silicon platforms. The extent of the resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
508
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 490 publications
(518 citation statements)
references
References 62 publications
(80 reference statements)
7
508
1
2
Order By: Relevance
“…To verify that it is the proton and not negative hydrogen ion (such as observed in YH 3-d ) 25 or oxygen vacancies 26 , which diffuses in SNO and also to demonstrate a proof-of-concept solid-state field effect device, a proton-gated transistor is fabricated, as shown in Fig. 6a.…”
Section: Doping-induced Phase Transition By LI and Mg Intercalationmentioning
confidence: 99%
“…To verify that it is the proton and not negative hydrogen ion (such as observed in YH 3-d ) 25 or oxygen vacancies 26 , which diffuses in SNO and also to demonstrate a proof-of-concept solid-state field effect device, a proton-gated transistor is fabricated, as shown in Fig. 6a.…”
Section: Doping-induced Phase Transition By LI and Mg Intercalationmentioning
confidence: 99%
“…Carrier doping by electrostatic gating or chemical substitution is an active field to modify electronic properties of nickelates [11][12][13][14][15] at the same time serving as a tool to understand and possibly control the metal insulator transition (MIT) phenomenon in nickelates. Earlier studies regarded nickelates as charge transfer insulators 16 whereas in recent works, the origin of insulating phase in nickelates has been attributed to charge disproportionation of the Ni site with an accompanying structural change from orthorhombic to monoclinic phase [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…8 The potential applications of these materials are wide-ranging, from sensors, optoelectronic switches to memory. 9,10 It is found that the MIT in nickelates could be tuned continuously by external electrical field. For example, via applying a static electric field on NdNiO 3 films with ionic liquid, the electric field induced shift of T MI results in a strong variation of the phase-dependent charge density.…”
Section: Introductionmentioning
confidence: 99%